IMPLEMENTASI KEBIJAKAN PERDA NOMOR 4 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH KOTA MAGELANG TAHUN 2011-2031 (Kajian Implementasi Kebijakan Larangan Mendirikan Bangunan di Sepanjang Sempadan Irigasi Kota Magelang) - Dionesia Bela Veda Kurnianingtyas; Sri Suwitri (Journal of Public Policy and Management Review, 2018)
There are still infraction in the form of various types of buildings at the irrigation border of Magelang City and some even stand on the irrigation canal of Magelang city become the background of this research. The objectives of the study were to describe and analyze the implementation of the ban building policy along the irrigation border of Magelang City. In addition, to identify and analyze any supporting and inhibiting factors that result in the policy of building ban along the irrigation border of Magelang city can not be implemented properly. This study uses the implementation theory of Van Meter and Van Horn and Daniel A. Mazmanian and Paul A. Sabatier where the variables taken are the characteristics of the problem and the policy environment with a qualitative approach. Data resource obtained from informants and documents. Data collecting techniques using interviews, observation, and documentation. Selection of informants using purposive and random sampling techniques. The results of the research shows that the obstacles to the implementation of this policy are the level of technical difficulties, plurality of target groups, socio-economic conditions, and public opinion, while the supporting factors are constituency groups and interest groups support. The recommendations that can be given are the need for supervision from non-governmental organizations, approaches to target groups, community empowerment, and providing flat.